2013
DOI: 10.3892/ol.2013.1156
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial pathology in breast cancer patients: Effect of different treatments on ultrasonographic, hysteroscopic and histological findings

Abstract: Breast cancer patients have an increased risk of endometrial pathology. To investigate whether the incidence of endometrial abnormalities and their clinicopathological features were affected by receiving tamoxifen (TAM), non-steroidal aromatase inhibitors (AIs) or no treatment (NT), 333 peri/postmenopausal breast cancer patients, who were referred to the Department of Gynecological, Obstetrical Sciences and Reproductive Medicine for gynecological assessment, were reviewed retrospectively. Transvaginal ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
(51 reference statements)
5
12
0
1
Order By: Relevance
“…In present study, endometrial cut off width was accepted as 5 mm, patients having values above ≥5 mm attempted invasive procedures (D&C, Hysteroscopic biopsy). In 27 (45.7%) of patients with endometrial thickenning (n=59), endomtrial pathologies were detected and it was consistent with literature ( 12 ) . But on the other hand, more than half of the patients (n=32, 54.3%) had invasive procedures although they didn’t have an underlying endometrial pathology.…”
Section: Discussionsupporting
confidence: 90%
“…In present study, endometrial cut off width was accepted as 5 mm, patients having values above ≥5 mm attempted invasive procedures (D&C, Hysteroscopic biopsy). In 27 (45.7%) of patients with endometrial thickenning (n=59), endomtrial pathologies were detected and it was consistent with literature ( 12 ) . But on the other hand, more than half of the patients (n=32, 54.3%) had invasive procedures although they didn’t have an underlying endometrial pathology.…”
Section: Discussionsupporting
confidence: 90%
“…This may be attributed to the non-endometrioid histological subtypes with a poorer prognosis among long-term tamoxifen users (39,45,55). However, there have been studies which indicated that the incidence of endometrial abnormalities and their clinicopathological characteristics were independent of tamoxifen use (56). In a recent retrospective study that investigated whether the incidence of endometrial abnormalities and their clinicopathological characteristics were affected by receiving tamoxifen, non-steroidal AIs or no treatment, Le Donne et al (56) reported cancer in 3.8% of the cases in the tamoxifen group and 11.1% of the cases in the no treatment group.…”
Section: Risks Following Hormonal Therapy Solid Cancersmentioning
confidence: 88%
“…However, there have been studies which indicated that the incidence of endometrial abnormalities and their clinicopathological characteristics were independent of tamoxifen use (56). In a recent retrospective study that investigated whether the incidence of endometrial abnormalities and their clinicopathological characteristics were affected by receiving tamoxifen, non-steroidal AIs or no treatment, Le Donne et al (56) reported cancer in 3.8% of the cases in the tamoxifen group and 11.1% of the cases in the no treatment group. Slomovitz et al (57) reported that females who developed endometrial cancer following a diagnosis of BC were at an increased risk of developing the high-risk histological subtypes, independent of tamoxifen use.…”
Section: Risks Following Hormonal Therapy Solid Cancersmentioning
confidence: 99%
“…Postoperative adjuvant systemic therapy prolongs survival in selected women with breast cancer and reduces the odds of death by 25% per year [ 3 ]. Tamoxifen is widely used as hormonal therapy in both, pre- and postmenopausal women with breast cancer and effectively reduces the risk of recurrence and mortality [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%